Possibilities for debelopment of tourism in the city of Turkestan (Journal of Economic Research & Business Administration, 2015)
In Republic Kazakhstan to develop religious tourism is main question. In it the article importance of tourism I examines economic functions. And also to the volume pointing works and activity, that was executed tourist by firms on sides of clothing Kazakhstan, to discuss done. In Kazakhstan enterprise in industry of tourism possibilities дамуна associate development of evening him given. Move religious tourism questions on to develop. Possibilities development tourist activity in city of Turkestan very much. Осыған discusses according to tourist to the chances Turkestan in accordance composition examination done. Mechanisms development tourist activity in city of Turkestan in result of that given. It presence of suggestions is need to develop nowaday economy of tourism. To tourism Because investment, that was inlaid, territorial economy and and state to the economy the impression your of оң touches. Therefore question investment attractiveness management on edge of Turkestan economy.
Keywords: tourism; inbound tourism; regions-leaders; accommodation; transportation; tourism product